Matters of the Heart: Grief, Morbidity, and Mortality. (June 2020) - Fagundes, Christopher P.; Wu, E. Lydia
Spousal bereavement is associated with elevated risk of morbidity and mortality. Several well-regarded multidisciplinary research teams have investigated the biopsychosocial processes underlying why widows and widowers are at elevated physical-health risk. Here, we review research from multiple investigators showing that, on average, widows and widowers exhibit maladaptive patterns of autonomic, neuroendocrine, and immune activity compared with matched comparison subjects. Widows and widowers also exhibit poorer health behaviors than they did before their spouse's death, and the considerable variation in postloss psychological-adjustment trajectories among widows and widowers likely corresponds to physical-health risk trajectories. Yet there is little biobehavioral research on patterns of change in physical-health risk after the death of a spouse. We summarize recently published work demonstrating how attachment theory can characterize and predict individual differences in physical-health biomarkers, highlighting the need for a biopsychosocial approach to understanding and characterizing postloss trajectory patterns. We conclude by discussing the possibility that this line of inquiry could help researchers, and ultimately providers, identify adjustment trajectories earlier and thus deliver appropriate interventions when they are most needed.